Inventory of Pest Types Attacking Canary Plants (Canarium indicum L) in Wail Matai Hamlet, Morella Village, Leihitu District - Kleopatra Tehupelasury; Cornelia Wattimena; Fransina Latumahina (Tropical Small Island Agriculture Management, 2026)
The research was conducted in July 2025 using an inventory method by establishing observation transects measuring 100 m in length and 20 m in width. Pest sampling was carried out using several techniques, including hand collecting, pitfall traps, sweep nets, and bait traps. Data analysis was performed by calculating the intensity of pest attacks and the percentage of infestation area on observed plants. The results showed that three main pest species attacked candlenut plants: termites (Cryptotermes sp.), ambrosia beetles (Xylosandrus crassiusculus), and wood grasshoppers (Valanga nigricornis). The highest damage intensity was caused by wood grasshoppers at 26.12%, categorized as moderate damage, while ambrosia beetles caused 4.36% damage and termites 1.10%, both categorized as minor damage. The percentage of infestation area across five observation plots ranged from 50.00% to 69.57%, classified as moderate to severe infestation. The high level of pest infestation was influenced by environmental factors such as temperature, humidity, food availability, and habitat conditions that support insect population development. In conclusion, pest attacks on candlenut plants in Wail Matai Hamlet are relatively high, particularly caused by wood grasshoppers that damage the leaves. Therefore, integrated pest management and regular monitoring are necessary to prevent further damage to candlenut plants in the area.